Biomechanically designed Curve Specific Corrective Exercise for Adolescent Idiopathic Scoliosis gives significant outcomes in an Adult: A case report - Maharathi, Sujata; Iyengar, Raju; Chandrasekhar, Patnala (Frontiers in Rehabilitation Sciences, 2023)
Background This study presents findings on improvements to the Frontal and Sagittal Cobb angle, Global Spinal balance, and lung function parameters (FEV1, PEF) in an adult male with idiopathic scoliosis suffering from pain during ADL and sports activities who was treated with a biomechanically designed exercise protocol. Case Presentation The 26-year-old male reported upper and middle back pain which worsened when playing cricket. Whole spine standing x-Ray AP view revealed a right thoracic Scoliosis (Lenke 1 curve) of Cobb angle 48.6° with left lumbar compensatory curve of 24.7°, Thoracic hypo kyphosis of 9.9°, and VAS rating for pain of 8. The patient was treated with myofascial release, stretching, aerobics, strengthening exercises, “Breathing with core” for stabilization, and biomechanically designed curve specific corrective exercises. Results Re-assessment 32 weeks post intervention demonstrated significant reduction in the major Cobb angle by 13.8°, minor Cobb angle by 9.5°, Thoracic hypokyphosis normalized to 37.8°, Coronal balance improved by 17.4 mm, Sagittal balance regained by 4.2 mm, Spine ROM improved by a total of 6.5 cm, Enhancement of pulmonary function of FEV1 by 7% and PEF by 18 litres/min, and dramatic improvement in aesthetics and pain perception. Conclusion The biomechanically designed exercise protocol helped straighten the curve through curve specific corrective exercises and stabilized the curve by “Breathing with core”. It also treated the associated signs and symptoms of spinal pain syndrome by myofascial release and proper ergonomics, pulmonary dysfunction by aerobics, and muscle tightness and weakness (due to altered length-tension) by stretching and strengthening.